Così fan tutte [videorecording (DVD)] : dramma giocoso in due atti - Da Ponte, Lorenzo, 1749-1838; Hampe, Michael, 1935-2022; Catani, Ilio; Dessì, Daniela; Ziegler, Delores; Corbelli, Alessandro; Kundlak, Jozef; Scarabelli, Adelina; Desderi, Claudio; Muti, Riccardo; Pagano, Mauro, 1951-1988; Mozart, Wolfgang Amadeus, 1756-1791 (La Scala collection., 2004)
"Daniela Dessì and Delores Ziegler lead the cast in Mozart's brilliant and witty opera as the two women whose faithfulness in the face of romantic love is ruthlessly tested in Da Ponte's comic tale. Mozart lavishes some of the finest music ever written on the unfolding story of the two sisters' chaotic and fickle love affairs with their two Italian army officers."--Container.